Atopic eczema and fracture risk in adults: A population-based cohort study - Lowe, Katherine E. (J Allergy Clin Immunol, 2020)
BACKGROUND: Limited evidence suggests increased fracture risk in people with atopic eczema. Any link could have substantial effect; atopic eczema is common, and fractures have associated morbidity and mortality. OBJECTIVE: We sought to examine whether atopic eczema is associated with fracture and whether fracture risk varies with eczema severity. METHODS: We performed a matched cohort study set in primary care (Clinical Practice Research Datalink GOLD 1998-2016) and linked hospital admissions data (Hospital Episode Statistics), including adults (≥18 years old) with atopic eczema matched (by age, sex, general practice, and cohort entry date) with up to 5 individuals without eczema. We estimated hazard ratios (HRs) from stratified Cox regression comparing risk of major osteoporotic (hip, pelvis, spine, wrist, and proximal humerus) fractures individually and any fracture in those with and without atopic eczema. RESULTS: We identified 526,808 people with atopic eczema and 2,569,030 people without atopic eczema. Those with eczema had increased risk of hip (HR, 1.10; 99% CI, 1.06-1.14), pelvic (HR, 1.10; 99% CI, 1.02-1.19), spinal (HR, 1.18; 99% CI, 1.10-1.27), and wrist (HR, 1.07; 99% CI, 1.03,-1.11) fractures. We found no evidence of increased proximal humeral (HR, 1.06; 99% CI, 0.97-1.15) fracture risk. Fracture risk increased with increasing eczema severity, with the strongest associations in people with severe eczema (compared with those without) for spinal (HR, 2.09; 99% CI, 1.66-2.65), pelvic (HR, 1.66; 99% CI, 1.26-2.20), and hip (HR, 1.50; 99% CI, 1.30-1.74) fractures. Associations persisted after oral glucocorticoid adjustment. CONCLUSIONS: People with atopic eczema have increased fracture risk, particularly major osteoporotic fractures.